2011
DOI: 10.3233/bmr-2011-0279
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of lumbosacral transforaminal epidural steroid injections: A comprehensive literature review

Abstract: This systemic review included prospective, retrospective and randomized clinical trials showing that there was strong evidence for transforaminal injections in the treatment of lumbosacral radicular pain for both short term and long term relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 21 publications
2
32
1
2
Order By: Relevance
“…While it is commonly known that TAESI is effective in the case of spinal stenosis and unsuccessful low back surgery etiology, [13,[21][22][23] it has been shown to be particularly more effective in discogenic low back pain. [13,24,25] In the present study, 85% of the patients suffered from pain stemming from lumbar disc herniation while 15% had diagnoses of unsuccessful back surgery and spinal stenosis. Another factor that similarly determines the effectiveness of TAESI is the duration of pain patients experience before the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…While it is commonly known that TAESI is effective in the case of spinal stenosis and unsuccessful low back surgery etiology, [13,[21][22][23] it has been shown to be particularly more effective in discogenic low back pain. [13,24,25] In the present study, 85% of the patients suffered from pain stemming from lumbar disc herniation while 15% had diagnoses of unsuccessful back surgery and spinal stenosis. Another factor that similarly determines the effectiveness of TAESI is the duration of pain patients experience before the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Benny reviewed the efficacy of epidural injection and concluded that there was strong evidence for transforaminal injections in the treatment of LSR pain for both short term and long term relief (Benny & Azari 2011). Once the epidural injection works for pain relief of these patients, repeated injection was suggested if it recurs.…”
Section: Epidural Steroid Injection and Diagnostic Imagingmentioning
confidence: 99%
“…Pedicle width narrowing and neuroforamen compromise can be seen on CT or MRI. The treatment choices for neurogenic pain before shifting to surgery includes epidural neuroforamen steroid injection (Benny & Azari 2011) selective nerve block (Thackeray et al, 2010) and RF for adjacent DRG (Van Boxem et al, 2011).…”
Section: Neurogenic Low Back Painmentioning
confidence: 99%
“…Оскільки в механізмі формування бо-льового синдрому провідним є фактор запалення, ЕІ лікарського засобу СП справляє позитивний вплив шляхом блокування рецепторів уражених хребцевих сегментів, а також через дію в зоні диско-радику-лярного конфлікту, сприяє зменшенню вираженості чи усуненню запальної реакції, яка відіграє важливу роль у формуванні больового синдрому. У проспек-тивних дослідженнях відзначені різні результати щодо ефективності ЕІ СП у лікуванні радикулярних синдромів [10][11][12][13][14][15].…”
unclassified